2019
DOI: 10.1038/s41592-019-0617-2
|View full text |Cite|
|
Sign up to set email alerts
|

Nanopore native RNA sequencing of a human poly(A) transcriptome

Abstract: High throughput cDNA sequencing technologies have advanced our understanding of transcriptome complexity and regulation. However, these methods lose information contained in biological RNA because the copied reads are often short and because modifications are not retained. We address these limitations using a native poly(A) RNA sequencing strategy developed by Oxford Nanopore Technologies (ONT). Our study generated 9.9 million aligned sequence reads for the human cell line GM12878, using thirty MinION flow cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
480
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 509 publications
(546 citation statements)
references
References 55 publications
(62 reference statements)
24
480
1
Order By: Relevance
“…It is noteworthy, that a minimum aligned length of about 100 nt appears in the data sets (see Supplementary Fig. 3d) when using the native RNA sequencing protocol and minimap2 as mapping tool 16,40,56 . Unaligned reads had a median read length of 191 nt, in contrast to 572 nt for aligned reads (all data sets combined) suggesting that short reads could not be aligned properly.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It is noteworthy, that a minimum aligned length of about 100 nt appears in the data sets (see Supplementary Fig. 3d) when using the native RNA sequencing protocol and minimap2 as mapping tool 16,40,56 . Unaligned reads had a median read length of 191 nt, in contrast to 572 nt for aligned reads (all data sets combined) suggesting that short reads could not be aligned properly.…”
Section: Resultsmentioning
confidence: 98%
“…The key steps of the library preparation are shown in Fig. 1a: after enzymatic polyadenylation, the RNA is reverse transcribed to increase sequencing throughput (recommended by ONT) 16 . Subsequently, a motor protein is added that feeds the RNA into the Nanopore.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our protocol identifies low or non-penetrant allele-specific alternative splicing events through bioinformatic analysis, and either q-RT-PCR, exon microarrays or RNAseq data analysis. Allele-specific splicing can also be determined by full-length alternative isoform analysis of RNA (or FLAIR [Workman et al 2019]). Differentiated splice forms are associated with specific alleles in heterozygotes with exonic SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the utility of long-read approaches in capturing full-length mRNA isoforms, by constructing isoforms missed by short-read assembly methods (Oikonomopoulos et al, 2016;Byrne et al, 2017;de Jong et al, 2017;Tang et al, 2018;Workman et al, 2019). Moreover, long-read approaches have already been conducted using RNA derived from primary tumor samples harboring SF3B1 mutations, demonstrating its effectiveness in capturing mutant splicing factor transcriptome alterations (Tang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%